Empowering MSME Communities to Enhance Batam's Local Product Marketing Based on Artificial Intelligence - Friadi, John; Windayati, Diana Titik; Made, Abdul Malik; Kurniawati, Ely; Muhammad Fikry Ananda Syaheza; Ahmad Fuad; Nur Andini Rianti (Pascasarjana Universitas Mataram, 2025)
Digital marketing is the application of digital technology to bring online sales (channels) to the market (websites, email, databases, digital TV, and other innovations such as blogs, feeds, podcasts, and social media) and contribute to the success of business operations. The purpose of this activity is to increase understanding among MSME actors, particularly Ananda Brownies Kukus-Batam, and the management of e-commerce websites for improving the marketing and sales of MSME products. The material will be presented in the form of a seminar. The seminar format will be used by the speaker to deliver the activity material, followed by discussions and simulations. The training activity provides benefits in improving the understanding of MSME actors about digital marketing and e-commerce website management. The digital marketing socialisation activity was conducted at Ananda Brownies Kukus, Batam, in the form of socialisation, creating an artificial intelligence chatbot-based e-commerce website for MSMEs, and training them in managing the website, to empower MSMEs to improve their marketing and sales.